INTERAKSI SOSIAL ANAK JALANAN DI LAMPU MERAH SKA PEKANBARU - Erma Sopianti; Rosmawati Rosmawati; Roby Maiva Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to understand and clearly describe the description and social interactions of street children at the SKA Pekanbaru traffic lights. The research subjects were three street children at the SKA Pekanbaru red light. The research method used a qualitative approach with descriptive research type. Data collection techniques in the form of observation, interviews, and documentation. The data analysis techniques used in this study were data reduction, data presentation, and conclusion drawing. Street children at the SKA Pekanbaru red light are aged 7 to 12 years, activities carried out on the streets are selling tissue and busking. Street children at the SKA Pekanbaru red light are street children who no longer go to school. Street children interact well with their peers, the patterns of social interaction between street children and peers which include cooperation, accommodation, assimilation and acculturation, competition and conflict have been well established. Street children and their peers have never had any significant conflicts or disputes, the dominant aspect of street children's social interaction with peers is the cooperation and acculturation of children with their peers, accommodation, competition, and conflict.Key Words: An Overview, Social Interaction, Street Children